The characteristics and the legal nature of the supervisory and resolution handbook of the EBA - Zoi Jenny Giotaki; Pauline de la Bouillerie; Rafael Nebot Seguí (European Banking Authority, 2023)
Article 16 of the EBA Founding Regulation enables the EBA to issue guidelines and recommendations, while Articles 8 (1) (aa) and (ab) and 29 (2) of that Regulation enable it to develop a handbook for supervision and resolution. The European Court of Justice (ECJ or Court, hereinafter), in its recent case-law, dealt extensively with the legal nature of guidelines. In this paper, we discuss the characteristics and the legal nature of the handbook, and we try to determine which of the principles set out in this case law for the guidelines should also be relevant for handbook
Keywords: G1; G18; G2; K00; K10; K19; K20; K29; K39; K40; 330; Soft law; handbook; guidelines; binding or non-binding nature; reviewability and preliminary ruling; ECJ